PERSEPSI WISATAWAN TERHADAP WISATA SELFIE SEBAGAI DAYA TARIK WISATA DESA WANAGIRI SUKASADA BULELENG BALI - Ni Kadek Widyastuti; Ni Luh Christine Prawita Sari Suyasa (Forum Manajemen STIMI Handayani Denpasar, 2019)
The purpose of this research is to identify tourists perception of wisata selfie as a tourist attraction.The potential of the village that has concept 4A (attraction, accessibility, amenities, dan Ancillary).As the respondents were 30 foreign and domestic travelers. Sampling is done by accidental sampling technique.The results show the Indicator of the perception in terms of tourist attractions variables, that gaining excellent ratings is the photography, with an average score of 4.5. Indicator of the accessibility variable that gain the excellent amenities is the location of objects with an average score of 4,3. Indicator of the amenities variable that gain the good assessment is the hotel, souvenir market, and restuarant with an average score of 4,1.The last variable is tourism organizations and indicator that gain good perception is the cleanliness, Security, Promotion and Information for Tourist with a score average of 4.0, 3,9 and 3,8. Based on the research results, the existence of Wanagiri village as a tourist attraction overall gotgood perception assessmentand mustbe followedup indicators that is considered badbytherespondents, inorder to improve the assessment perception of visitors.